A randomized controlled trial of group psychological intervention combined with medication for treating adolescent depression - Yu, Xinming; Chen, Zijun; Wang, Bin; Zheng, Ke; Liang, Yong; Guo, Jian; Li, Shikang; Yu, Liang (Frontiers in Psychology, 2025)
ObjectiveA study of the effects of group psychotherapy on depression and anxiety in adolescents.MethodsNinety-two adolescent depression patients attending a city mental health center from May 2022 to December 2024 were selected for the study, and a randomized controlled trial design was used with 46 cases in each group. The patients in the observation group were treated with group psychotherapy combined with medication. The patients in the control group were treated with medication, for four consecutive weeks, and t-tests and chi-square tests were used to compare the differences in the rates of HAMA and HAMD-17 score reduction between the two groups.Results(1) The difference in HAMD-17 scores between the two groups at baseline was not statistically significant (Z = −0.455, p = 0.649). In contrast, the difference in HAMA scores between the two groups at baseline was statistically significant (Z = −2.120, p = 0.034). Four patients in each of the two groups dropped out of the treatment, resulting in a total dropout rate of 8%. (2) At the end of the 4-week treatment, the HAMA and HAMD-17 scores of patients in the two groups were significantly lower than those at baseline, and the difference in the rate of reduction in HAMA and HAMD-17 scores before and after the treatment between the observation group and the control group (89.1% vs. 34.8, and 97.8% vs. 80.4%) was statistically significant (χ2 = 28.82, p < 0.001; χ2 = 7.18, p = 0.007), indicating clinically meaningful improvement as both rates far exceed the 50% threshold for treatment response.ConclusionAfter group psychotherapy combined with medication to treat depression symptoms in adolescents is more effective, it can effectively accelerate the recovery of the disease, improve negative emotions, and reduce the recurrence of the disease.